ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE (ICD) - Nineng Setianingsih, 12.05.52.0144; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2016)
The purpose of this study was to examine and analyze the effect of firm size, firm age, independent commissioners, leverage, profitability and oenership’s concentration of the intellectual capital disclosure. The sample of this study were companies that listed in Indonesian Stock Exchange (IDX) which the category were manufacture companies. The population in this research is manufacture companies that listed in Indonesia Stock Exchange in 2012 to 2014. Sampling was done using purposive sampling method. To test and analyze the influence between variables using multiple regression analysis. The results showed that the firm size and profitability has significant positive effect to the intellectual capital disclosure; firm age and independent commissioners has negative significant effect to the intellectual capital disclosure; leverage has positive effect and no significant to the intellectual capital disclosure; while the ownership’s concentration has no significant effect to the intellectual capital disclosure.Keywords: Company Size, Company Age, Independent Commissioners, Leverage, Profitability, Ownership Concentration, Intellectual Capital Disclosure